Gender Influences on Local Botanical Knowledge: A Northeast Brazil Study - Gomes, Celiane da Silva Ribeiro; Gama, Aline Dourado Sena; Cantalice, Aníbal da Silva; Mata, Paula Thayanne; Silva, Taline Cristina; Muniz de Medeiros, Patrícia (Ethnobotany Research and Applications, 2024)
Background: Ethnobotanical studies commonly employ the gender variable to understand how knowledge about medicinal plants is structured. However, most focus specifically on the number of species known among men and women, with limited attention to issues such as collection location, species endemism, and the repertoire of medicinal plants. This study primarily seeks to understand if there are differences in various types of knowledge and in the composition of known and used medicinal species between genders. Methods: The study was conducted in the rural community of Morrão de Cima, Bahia, Brazil. We gathered information about the knowledge and use of medicinal species, including details on collection sites, through semi-structured interviews. To answer our questions, we used generalized linear models and a multivariate permutational analysis of variance. Results: We found no significant difference in the total number of known medicinal species between genders. However, women showed greater knowledge of species close to their homes and exotic species, while men demonstrated more knowledge of species in forested areas and native species. We also observed a significant difference between the species known and used by men and women. Conclusions: Our findings emphasize the need to use various knowledge metrics for a deeper understanding of the relationship between medicinal species knowledge and gender. Differences in the composition of medicinal plants between men and women highlight the heterogeneity of knowledge, underscoring the essential role of both genders in shaping local medical systems, resulting from the health/disease dynamics among genders. Keywords: Ethnobotany; Local ecological knowledge; Medicinal plants; Composition; Knowledge and use.